2022
DOI: 10.1002/cli2.45
|View full text |Cite
|
Sign up to set email alerts
|

Cultural heritage and risk assessments: Gaps, challenges, and future research directions for the inclusion of heritage within climate change adaptation and disaster management

Abstract: Cultural heritage shapes our identity, delivers capacities, and exposes vulnerabilities, yet cultural heritage value and vulnerability are largely missing from conventional risk assessments. Risk assessments are a fundamental first step in identifying effective mechanisms for Climate Change Adaptation (CCA) and disaster management. However, by ignoring the influence of heritage, decision makers are limiting their understanding of risk and therefore opportunities vital for building and maintaining local resilie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…CVI also addresses the vulnerability of heritage to climate risks but not the likelihood of the risks occurring. Crowley et al [50] advise the adoption of a climate risk assessment method that allows active participation of local community members to address the top-down approaches that are prevalent in managing climate risks to heritage. These characteristics of ABCCH made it ideal for the current study, enabling maximum inclusion and active participation of non-climate experts and members of local communities in all phases of the process, i.e., from the planning to the monitoring and evaluation phases.…”
Section: Risk Analysismentioning
confidence: 99%
“…CVI also addresses the vulnerability of heritage to climate risks but not the likelihood of the risks occurring. Crowley et al [50] advise the adoption of a climate risk assessment method that allows active participation of local community members to address the top-down approaches that are prevalent in managing climate risks to heritage. These characteristics of ABCCH made it ideal for the current study, enabling maximum inclusion and active participation of non-climate experts and members of local communities in all phases of the process, i.e., from the planning to the monitoring and evaluation phases.…”
Section: Risk Analysismentioning
confidence: 99%
“…For instance, the study by Lawson et al (2020) shows that, in the Lawra and Nandom districts of UWR, socio-economic status and decision-making power influence the vulnerability of households to the impacts of climate change. Moreover, the cultural factors intersect with climate vulnerabilities and have implications for climate action (Crowley et al, 2022). Dakurah (2018) reported that farmers in Northern Ghana still cultivate a traditional variety of groundnut (dagarasinkaa), even though it has low yields, and less market value compared to the hybrid variety.…”
Section: Changing Climate Social Transformations and The Complexity O...mentioning
confidence: 99%
“…However, based on the results of an interview with one of the informants in the field, it is known that business actors and the local government have agreed on the area for the development of shrimp ponds and the chicken-trading industry to be allocated in the south side of JJLS. The results of community participation and agreement can be used to compile land use arrangements to reduce disaster risk [56]. Open shrimp ponds would be better devel-oped with the concept of side-by-side with forestry/plantation plants (silvofishery) as a tsunami mitigation strategy [43].…”
Section: Tsunami Hazardmentioning
confidence: 99%